Polymorphism in Intron-I of Myostatin gene and its association with estimated breeding values of growth traits in Baluchi sheep (Ovis aries) - ANSARY, M; TAHMOORESPUR, M; NASSIRY, M R; TAHERI, A; VALEH, M VAFAYE (The Indian Journal of Animal Sciences, 2011)
GDF8 gene is associated with skeletal muscle mass in farm animals. The association of GDF8 gene polymorphism with growth traits including birth weight, weaning weight, 6 months weight, 9 months weight and yearling weight in 112 individuals of superabundant sheep in Iran (Baluchi) was investigated. Polymerase chain reaction - single strand conformation polymorphism (PCR-SSCP) method was employed in screening for genetic variation. Three unique SSCP patterns (P1, P2 and P3) for intron1 region of GDF8 gene were observed. Breeding values of growth traits were estimated by using the best linear unbiased prediction based on an animal model with a relationship matrix. Studied growth traits were examined for association analysis. Our findings suggested that the P1 genotype has the highest body weight and the highest additive estimated breeding value for the weaning weight trait. Hence, the intron1 region of GDF8 variants could serve as a genetic marker for Baluchi sheep breeding and genetics. The other traits showed no relationship to the genotypes examined.